A Comparative Study of Quraish Shihab and Nasaruddin Umar’s Qur’anic Exegesis on Love and Tolerance - Aprilianti, Anisatul Fikriyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Studies on love and tolerance in Qur'anic interpretation have been dominated by the normative-theological perspectives of Middle Eastern exegetes, until now, which do not accommodate social-cultural contexts and local wisdom. This is because there has been little exploration of the dimensions of interpretation based on local wisdom that are relevant to the discourse of global harmony. This study aims to fill this gap through a comparative analysis of the thoughts of M. Quraish Shihab and Nasaruddin Umar. The method used is a literature study with a qualitative-comparative approach to the works of Quraish Shihab, Tafsir al-Mishbah, and Nasaruddin Umar, such as Deradikalisasi Pemahaman Al-Qur'an (Deradicalization of the Understanding of the Qur'an). The results show that Quraish Shihab and Nasaruddin Umar share the view that local values such as mutual cooperation and deliberation can serve as the foundation for global peace. The difference in their thinking is that Quraish Shihab emphasizes universal compassion and humanity, while Nasaruddin Umar emphasizes equality and plurality. Their thinking offers a model of contextual interpretation that is relevant to the contemporary world and contributes significantly to the development of peaceful, inclusive, and transformative Islamic studies. This study not only contributes to the understanding of Indonesian Qur’anic hermeneutics but also proposes an integrative model of contextual exegesis relevant to global ethical discourse